Exploring Early Mobilization Practices in Adult Intensive Care Units in Jordan: A Cross-Sectional Survey - Wshah A; Obaidat S; Shallan AI; Muhsen A; Bin Sheeha B; Alkasassbeh A; Wshah S; Al Hadidi ARB; Altaim TA; Sawafta B; Alqallab S (Journal of Multidisciplinary Healthcare)
Adnan Wshah,1 Sakher Obaidat,1 Amjad I Shallan,1 Ahmad Muhsen,1 Bodor Bin Sheeha,2 Asmaa Alkasassbeh,3 Shadi Wshah,4 Abdel Razzaq Bassam Al Hadidi,5 Thamer A Altaim,1 Batul Sawafta,1 Salsabeel Alqallab6 1Department of Physical Therapy, Faculty of Applied Medical Sciences, The Hashemite University, Zarqa, Jordan; 2Department of Rehabilitation Sciences, College of Health and Rehabilitation Sciences, Princess Nourah Bint Abdulrahman University, Riyadh, Saudi Arabia; 3Physiotherapy Department, Faculty of Allied Medical Sciences, Isra University, Amman, Jordan; 4Physical Therapy Department, Jordanian Royal Medical Services, Amman, Jordan; 5Department of Physical Therapy, School of Rehabilitation Sciences, The University of Jordan, Amman, Jordan; 6Al Patrawi Physiotherapy Center, Zarqa, JordanCorrespondence: Adnan Wshah, Department of Physical Therapy, Faculty of Applied Medical Sciences, The Hashemite University, P.O box 330127, Zarqa, 13133, Jordan, Email adnan.wshah@hu.edu.joBackground: Prolonged immobilization in critically ill patients in the intensive care unit (ICU) is associated with adverse health outcomes, such as ICU-acquired weakness (ICU-AW), pressure ulcers, and decreased cardiopulmonary function. Early mobilization has been shown to be an important intervention to mitigate these effects; however, there is limited information regarding its implementation in ICUs in Jordan. This study aimed to explore early mobilization practices in adult ICUs in Jordan and identify common strategies employed by healthcare professionals.Methods: An observational, cross-sectional survey was conducted among healthcare professionals working in various ICUs across Jordan. A structured online questionnaire collected data on participants’ demographics, patient selection criteria for early mobilization, and early mobilization practices. Descriptive and inferential statistics (Kruskal‒Wallis, Mann‒Whitney, Chi‒square, and Fisher’s exact tests) were used, with significance at p < 0.05.Results: A total of 200 surveys were completed, primarily from physiotherapists (34.5%) and nurses (21%). The most common early mobilization strategies reported were positioning (19.3%), active mobilization (14.4%), and passive mobilization (13.1%). The majority of respondents combined early mobilization with secretion drainage activities. Respiratory stability was the most frequently cited criterion for determining patient eligibility. A significant proportion of respondents (36%) reported the absence of standardized protocols for early mobilization in their ICUs.Conclusion: Early mobilization is recognized among healthcare professionals in Jordan as an essential practice in ICUs, but there are variations in its implementation and a lack of standardized protocols. These findings highlight the need for clear guidelines and training initiatives to support consistent practice. Future research should investigate barriers to early mobilization, particularly in high-risk populations, to improve outcomes in critically ill patients.Keywords: early mobilization, exercise, healthcare professionals, intensive care unit